ADHD and Brain Anatomy: What Do Academic Textbooks Used in the Netherlands Tell Students?. (12th October 2019) - te Meerman, Sanne; Batstra, Laura; Freedman, Justin E.; Hoekstra, Rink; Grietens, Hans
Abstract : Studies of brain size of children classified with ADHD appear to reveal smaller brains when compared to 'normal' children. Yet, what does this mean? Even with the use of rigorously screened case and control groups, these studies show only small, average group differences between children with and without an ADHD classification. However, academic textbooks used in the Netherlands often portray individual children with an ADHD classification as having a different, malfunctioning brain that necessitates medical intervention. This conceptualisation of ADHD might serve professional interests, but not necessarily the interests of children.